Prospects of Using Poultry by-Products in the Technology of Chopped Semi-Finished Products - Zhumanova, Gulnar; Rebezov, Maksim; Assenova, Bakhytkul; Okuskhan, Eleonora (International Journal of Engineering and Technology, 2018)
In this paper the technology of preparation the protein-fat emulsion and its effect to sensory, physicochemical and microbial characteristics of meat cutlets are presented. The protein-fat emulsion consists of 75% of the chicken crests, 15% of the vegetable oil and 10% water. The protein, fat and ash content of emulsion are 9.53%, 6.38% and 0.95%, respectively. The amino acid composition of the protein-fat emulsion includes a complete set of essential amino acids - 36.2%. Adding of protein-fat emulsion as an ingredient in meat cutlets increase the total protein content, improves the sensory parameters and consistency of meat cutlets.Â Â